Exploring Psychosocial Issues of Breast Cancer: What Coping Mechanisms Have They Used to Manage Their Stressors? - Ibad, Muhammad Rosyidul; Katrina, Mery; Muhammad Ari Arfianto; Ariani, Tutu April (Journal of Ners and Midwifery, 2025)
One of the most common diseases causing death in women is mammary carcinoma which is the third largest cause of death in Indonesia after heart disease and stroke. Chemotherapy and surgery are treatment methods that have been widely used. The body image of patients who have undergone mastectomy will change as they no longer have breasts. The purpose of this study was to determine how coping mechanisms were used in patients suffering from carcinoma mammae post-mastectomy. This study used a qualitative-quantitative research design. The data was obtained through semi-structured interview guides and coping mechanism questionnaires as support. The data validity test method used triangulation of sources and methods. The data analysis in the study used domain analysis. The researcher analyzed the data using domain analysis and found seven main themes emotional distress when first diagnosed with Ca mammae, body image disturbance after mastectomy, breast loss after mastectomy, the use of active coping in seeking recovery, use of healthy lifestyle planning to reduce disease risk, use of religious coping mechanisms for illness perception, use of acceptance coping mechanism in illness. Some psychosocial problems such as mental emotional disorders such as severe stress, fear, and worry about the disease are often felt by patients. However, participants use adaptive coping mechanisms to adapt to psychosocial problems through the use of active coping, religion, planning, and being able to accept deficiencies in their body image.